18 Clinical Characteristics and Antihypertensive Agents Used at Hemodialysis Clinics in Jakarta. (November 2017) - Waren, Kalis; Wibisono, Prio; Japar, Karunia Valeriani; Tanzil, Sheila; Vatvani, Akhil Deepak; Lemuel, Theo Audi Yanto
Abstract : Background: Chronic kidney disease (CKD) has emerged as a public health challenge in developing countries like Indonesia. Hypertension as one of the most common etiology of CKD could also be a complication of CKD itself. Hypertension is seen in majority of patients undergoing hemodialysis and should be controlled properly in order to prevent major cardiovascular outcome and reduce mortality rate. Objective: To investigate the clinical characteristics and the types of antihypertensive agents used at hemodialysis clinics in Jakarta. Methods: This is a descriptive study that took place in 4 local hemodialysis clinics from October to December 2016. Clinical, laboratory data and antihypertensive medications used were recorded. Results: A total of 138 patients were included in our study, out of which 86(62.3%) were male. The mean age of the patients were 49.3(±12.4) years. The most common etiology of CKD was hypertension (56.5%) and diabetes (29.7%). The mean duration of HD was 38.6(1–216) months. There were 23(16.6%) patients with BMI >25 kg/m 2 . Median hemoglobin values were 8.3(1–11.8) mg/dl. The median creatinine levels were 9.71(2.8–31.4) mg/dl. The median sodium levels were 138(101–147) mEq/L.41(29.7%) patients had potassium greater than 5.0mEq/L. Median systolic BP pre and post HD was both 140mmHg. 106(76.8%) had hypertension, 46(33.3%) had diabetes mellitus, 24(17.3%) had hyperlipidemia. The median number of antihypertensive drugs were 2(1–4).43% received CCB, 32.5% received ACEI or ARB, 6.97% received beta blockers, 8.1% received alpha blockers and 9.3% received diuretics. Conclusion: Most of our patients use CCB, ACEI or ARB to control their blood pressure. By knowing the characteristics of the patients, we can treat the underlying causes better and prevent further complications from happening.